Pendekatan Literature Reviews dalam Keterlibatan Konsumen pada Sosial Media Instagram: Mengetahui Efek Customer Complaint terhadap Loyalitas Konsumen dan Kepuasan Konsumen - Dillah, Sahari Ayu Farrah; Kurniawati, Kurniawati; Siagian, Yolanda Masnita (Universitas Batanghari Jambi, 2025)
The development of the internet and digital technology currently makes it easier for consumers to convey consumer responses and satisfaction. Customer response in expressing dissatisfaction with a product or service due to a difference between expectations and the actual capabilities of a product or service offered. This will have a negative effect which is believed to affect consumer loyalty. This research discusses consumer involvement in providing complaints on Instagram social media, and whether it affects consumer satisfaction and loyalty. The research method used is a Systematic Literature Review (SLR) with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) analysis model. The research results show that consumer complaints given or disseminated on Instagram social media have an effect on consumer loyalty and consumer satisfaction.